2012
DOI: 10.1007/978-3-642-28830-2_18
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Context-Free Grammars Based on Parsing Generated Test Data

Abstract: Abstract. There exist a number of software engineering scenarios that essentially involve equivalence or correspondence assertions for some of the context-free grammars in the scenarios. For instance, when applying grammar transformations during parser development-be it for the sake of disambiguation or grammar-class compliance-one would like to preserve the generated language. Even though equivalence is generally undecidable for context-free grammars, we have developed an automated approach that is practicall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
4
3
1

Relationship

3
5

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 25 publications
0
11
0
Order By: Relevance
“…In general, the problem of determining whether 2 context‐free grammars are equivalent is undecidable but, in practice several techniques, have been successfully used for this purpose. ()…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In general, the problem of determining whether 2 context‐free grammars are equivalent is undecidable but, in practice several techniques, have been successfully used for this purpose. ()…”
Section: Resultsmentioning
confidence: 99%
“…In general, the problem of determining whether 2 context-free grammars are equivalent is undecidable but, in practice several techniques, have been successfully used for this purpose. 28,29 The analysis of the formulas in the dataset revealed that the majority are small and simple, but also that surprisingly large and complex formulas, with more than 50 functions or operations, exist. In terms of functionality, the majority of the formulas include at least one function or operation and almost half of them contain at least one constant.…”
Section: Resultsmentioning
confidence: 99%
“…Arguably, rule-based build systems are declarative in nature, except that they may insufficiently track dependencies so that incremental building and testing may fail to be sound or optimal. A declarative [4][5][6][7][8][9][10][11][12][13][14][15][16][17][18][19][20][21] approach to build management and configuration management has been proposed by Singleton and collaborators [50,9]; in particular, logic deduction (Prolog) is used to represent Make-like rules; soundness and optimality of incremental building is not addressed. The Haskell-based build tool Shake [44] incorporates dependencies that are retrieved while building.…”
Section: Declarative Build Managementmentioning
confidence: 99%
“…The computation of such distances can be as simple as the classic Levenshtein algorithm [Lev66] or involve something more advanced like longest common subsequence [GZ05]: ultimately, we want one that puts "expr" closer to "expression" than to "abcd", but even (modifications of) much more advanced techniques such as those relying on signature-based equivalence [Zay14c] or parser-based matching [FLZ12], could be applied here as well. The adviseFreshNonterminal function is somewhat more bulky and would not add much value to the paper -an interested reader is welcome to have a look at it, as well at other programmed negotiations, in the repository of SLPS [ZLvdS + 14].…”
Section: Advantages and Usesmentioning
confidence: 99%